Chemical composition and antimicrobial activity of the essential oils from stems and leaves of Michelia alba D.C. growing in Vietnam - Ha, Chu Thi Thu; Thai, Tran Huy; Diep, Le Ngoc; Thanh, Trinh Xuan; Thu Thuy, Dinh Thi; Tra, Nguyen Thanh; Thu Ha, Nguyen Thi (Academia Journal of Biology, 2018)
The chemical composition of the essential oils obtained by hydrodistillation of the stems and leaves of Michelia alba D.C. growing in North Vietnam was analyzed using GC/MS. In total, 28 compounds were identified in both stem and leaf oils, accounting for 99.33% and 99.54% of the oils, respectively. Linalool was the major component of both oils (80.65% and 72.89%, respectively), and other 22 compounds were also present as the constituents of both oils with varying amounts except 1,10-di-epi-cubenol present only in stem oil, whereas borneol (=endo-borneol), α-copaene, α-selinene and ethyl 2-phenylhexanoate were found only in leaf oil. In the stem oil, (Z)-β-ocimene (1.94%), (E)-β-ocimene (2.28%), β-caryophyllene (1.26%), (E)-nerolidol (1.15%), caryophyllene oxide (2.26%) and epi-α-muurolol (=T-muurolol) (1.80%) were present in sizeable amounts. The minor components detected in the leaf oil were (Z)-β-ocimene (1.73%), (E)-β-ocimene (2.28%), Cis-β-elemene (3.03%), β-caryophyllene (4.04%), α-humulene (1.44%), (E)-nerolidol (4.42%) and caryophyllene oxide (1.36%). Antibiotic activity of the essential oil samples was tested against Gram positive bacteria Staphylococcus aureus, Gram negative bacteria Escherichia coli, and yeast Candida albican using an agar disk diffusion method. The antimicrobial activity of leaf oil was stronger than that of stem oil, although both oils have significant inhibitory activity against all three microorganisms tested with the inhibitory zone diameters ranging from 15.5 to 46.5 mm.